2013
DOI: 10.1162/jocn_a_00483
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Amygdala Damage on Juvenile Rhesus Macaque Social Behavior

Abstract: The present experiments continue a longitudinal study of rhesus macaque social behavior following bilateral neonatal ibotenic acid lesions of the amygdala or hippocampus, or sham operations. Juvenile animals (approximately 1.5- 2.5 years of age) were tested in four different social contexts—alone, while interacting with one familiar peer, while interacting with one unfamiliar peer, and in their permanent social groups. During infancy, the amygdala-lesioned animals displayed more interest in conspecifics (index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
(64 reference statements)
7
44
1
Order By: Relevance
“…In fact the low levels of fear exhibited by the juvenile-lesioned animals along with other differences in social behavior suggest deficits in completely different domains of behavior (such as wariness and dominance) which are typically acquired during adolescence 77, 79 . Moreover, although the magnitude of these effects diminished over the course of development in both groups of monkeys distinct patterns in most functions did persist into adulthood suggesting that amygdala modulated social behavior in development has persistent effects 78, 80 …”
Section: The Role Of the Amygdalamentioning
confidence: 96%
See 1 more Smart Citation
“…In fact the low levels of fear exhibited by the juvenile-lesioned animals along with other differences in social behavior suggest deficits in completely different domains of behavior (such as wariness and dominance) which are typically acquired during adolescence 77, 79 . Moreover, although the magnitude of these effects diminished over the course of development in both groups of monkeys distinct patterns in most functions did persist into adulthood suggesting that amygdala modulated social behavior in development has persistent effects 78, 80 …”
Section: The Role Of the Amygdalamentioning
confidence: 96%
“…The interpretation of these discrepant findings is that the amygdala plays a developmentally specific role in guiding social learning. Animals that had very little social experience with an intact amygdala were unable to use the amygdala to guide behavior during early social interactions, and therefore failed to acquire rudimentary patterns of social behavior or social expectations and consequently were chronically socially dysfunctional, fearful and submissive 76, 78 . In contrast, juvenile animals who had a functional amygdala during early peer interactions established basic rules and expectations of peer behavior, and therefore were not fearful in a social context.…”
Section: The Role Of the Amygdalamentioning
confidence: 99%
“…For instance, recovery of fear learning deficits has been demonstrated in macaque monkeys (Kazama et al 2012) and human (Becker et al 2012) adults that sustained very early amygdala damage, but recovery does not occur when damage is incurred in adulthood (Antoniadis et al 2007(Antoniadis et al , 2009. While some social deficits persist throughout the lifespan in monkeys with neonatal amygdala lesions, social functioning is generally less disturbed in juveniles or adults that received amygdala lesions as neonates (Bliss-Moreau et al 2011;Bliss-Moreau et al 2013;Moadab et al 2015) relative to monkeys lesioned as adults (Adolphs 2010). These findings imply that some compensatory reorganization of neural circuitry over the course of development occurs as a consequence of early amygdala damage.…”
Section: Local and Remote Plasticity Following Lesionsmentioning
confidence: 99%
“…Few studies have shown that neonatal hippocampal damage yields abnormal emotional reactivity to objects and social partners (Bauman et al, 2004; Bliss-Moreau et al, 2010, 2011a, 2013), but normal HPA-axis response to pharmacological challenges assessed at 2.5-4.5 months after the lesion (Goursaud et al, 2006). Yet, none of these studies have investigated the impact of early hippocampal damage on both behavioral and physiological (HPA axis) stress reactivity.…”
Section: Introductionmentioning
confidence: 99%